Design, Fabrication, And Testing Of Simple Tool For Lodged Paddy Rice - Bahshon, Mohamad Hafizi (Universiti Sains Malaysia, 2022)
Lodged paddy rice occurs when plant stems weaken to the point they can no longer support the weight of the grain causing it to fall over. Lodging is increasingly important in rice cultivation as producers strive for the highest grain output yet, this adds to harvest time and expense and frequently results in considerable yield loss. Many alternatives have been taken to prevent the lodging problem such as the usage of chemicals based fertilizer and different method of sowing but unfortunately the problem still occur. Currently, there are no proper tool to solve the lodging problem. Instead, most of them are more to prevent the problem from happen rather than solve it. So, this project will aim to produce a simple tool that are cheap in price, environmentally friendly material, and easy to be used by the farmer to solve the lodged paddy rice problem. Design requirements obtained from the survey were then translate into design concept. The best design is selected based on designs pool and feedback from customer. From the produced prototype, assembly and time study depicted that the final product will surely able to help the farmer solve the lodged paddy rice problem while at the same time reduce the loss from lodging.